Characterization of commercial Sacha inchi oil according to its composition: tocopherols, fatty acids, sterols, triterpene and aliphatic alcohols - Ramos Escudero, Fernando (2019)
Sacha inchi oil (SIO) is one of the largest vegetable oil exports in Peru, used for consumption, in the food industry, cosmetics, and pharmaceuticals; it represents a significant economic income for producers. This study addresses the characterization and quantification of fatty acids, tocopherols, sterols, and alcohols of commercial Sacha inchi oils from Peru. Some of the SIO samples received had a high substance consistency, while others differed in the compounds studied. The results showed that some of the commercialized oils present high levels of γ-tocopherol and δ-tocopherol, while other samples had variable fatty acid compositions; especially in α-linolenic, linoleic, oleic and palmitic acids. Fourteen sterols and eleven alcohols were identified (β-sitosterol, stigmasterol, campesterol, Δ5-avenasterol, triterpene alcohol, lanosterol isomer 1 and cycloartenol) being the major components. Some SIO samples presented the following ratios: The δ-tocopherol/γ-tocopherol ratio was 0.33–0.81, ω-6/ω-3 ratio was 0.77 and a stigmasterol/campesterol ratio of 3.13. The presence of brassicasterol in some commercial oils indicates the addition of rapeseed or canola oil. Tocopherols, fatty acids, sterols and alcohol data provided a classification of SIO samples, by an efficient k-means clustering algorithm analysis. The ANOVA found significant differences between clusters for palmitic acid, oleic acid, γ-tocopherol, δ-tocopherol, campesterol and stigmasterol; these compounds could be used as markers of authenticity in commercial Sacha inchi oils.